CD‐sACE2 inclusion compounds: An effective treatment for coronavirus disease 2019 (COVID‐19). Issue 10 (17th April 2020) - Sun, Pengfei; Lu, Xiaosheng; Xu, Chao; Wang, Yanjin; Sun, Wenjuan; Xi, Jianing
Abstract: Coronaviruses are common human viruses and include the severe acute respiratory syndrome coronavirus (SARS‐CoV), the middle east respiratory syndrome coronavirus and the SARS‐CoV‐2. Coronaviruses mainly bind to transmembrane receptor proteins on the human cell membrane through spike proteins (S‐proteins), thus releasing the RNA of the virus into the interior of the host cell to cause an infection. In this article, we discuss the mechanism and production of cyclodextrin‐soluble angiotensin‐converting enzyme 2 (CD‐sACE2) inclusion compounds in the treatment of SARS‐CoV‐2 infections by blocking S‐proteins. On the basis of the current research evidence, we believe that CD‐sACE2 inclusion compounds have the potential to treat COVID‐19. We hope that our article can provide a theoretical basis for later experiments. Highlights: At present, there are no available drugs or vaccines that can treat or prevent coronavirus disease 2019 (COVID‐19) effectively. We introduce the mechanisms and drug fabrication methods of cyclodextrin‐soluble angiotensin‐converting enzyme 2 (CD‐sACE2) inclusion compounds for the treatment of COVID‐19. It is believed that CD‐sACE2 inclusion compounds can effectively treat COVID‐19.